Pelatihan Implementasi Kegiatan Pembelajaran Pada Kurikulum Merdeka PAUD - Ifadah, Ayunda Sayyidatul; Fitri Ayu Fatmawati (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
In the 2023-2024 academic year, registration will begin to open for institutions wishing to implement the Merdeka curriculum. One of them is that the Aisyiyah Bustanul Athfal 42 Griya Bunder Asri Gresik Kindergarten has not yet registered its institution in this academic year, so it is still using the 2013 curriculum. Based on these conditions, the Aisyiyah 42 Griya Bunder Asri Gresik Kindergarten will implement it, but in the process of studying the Merdeka curriculum, the principal feels that it is still not maximal. So there is a need for assistance from more competent parties. Based on this, we from the PIAUD study program offer community service as a form of collaboration between the Aisyiyah Bustanul Athfal 42 Griya Bunder Asri Gresik Kindergarten and the PIAUD Study Program in the form of training assistance as well as regarding the implementation of activities in the independent curriculum. This community service activity aims to provide educational assistance and training to Kindergarten Aisyiyah Bustanul Athfal 42 Griya Bunder Asri Gresik. The hope is that Kindergarten educators Aisyiyah Bustanul Athfal 42 Griya Bunder Asri Gresik will be able to understand and implement the Merdeka curriculum properly and correctly in accordance with government guidelines and Presentation in learning must prioritize the process and be packaged in play activities and games.